ChatGPT Penggunaan Artifficial Intelligence Terhadap Integritas Akademik dan Kesejahteraan Pribadi Mahasiswa : Penggunaan Artificial Intelligence Terhadap Integritas Akademik dan Kesejahteraan Pribadi Mahasiswa. - Norpi (Ra'ah: Journal of Pastoral Counseling, 2025)
This paper discusses the use of ChatGPT an artificial intelligence (AI) tool, on students’ academic integrity and personal well-being. Using a qualitative research method with a library research approach, it anlayses various related literatures to identity the benefits and risks of using ChatGPT in an academic context. The result showed that the development of AI including CharGPT can support students in understanding difficult material, completing assigments efficiently and reducing academic stress however, irresponsible use can threaten academic integrity through plagiarism and weaken critical and analytical thinking skills. In addition, dependence on these technologies can affect students’ self confidence and social interactions, which can negatively impact students’ well-being. Therefore, an ethical and responsible approach to the use of ChatGPT is needed, one which is to provide education on the limitations of the technology and emphasise the importance of integrity-based academic skills.